Design, Synthesis, and Biological Evaluation of Some Benzothiazolone Derivatives as Cholinesterase Inhibitors. Issue 46 (8th December 2022) - Alagöz, Mehmet Abdullah; Akkaya, Didem; Arslan, Gülnur; Uludağ, Berk; Özdemir, Zeynep; Barut, Burak; Önkol, Tijen; Sari, Suat
Abstract: In this study, nine new benzothiazolone derivatives (6 a –i ) were designed and synthesized to identify potent cholinesterase inhibitors. The compounds were tested in vitro against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) and found to be selective to BChE. Compound 6 f proved the most potent derivative (IC50 =12.25±0.23 μM) against BChE and was identified as a mixed‐type inhibitor with a K i value of 4.45±0.35 μM according to the kinetic studies. Molecular modelling suggested that the derivatives were druglike and non‐PAINS. Compound 6 f showed good fit in BChE active site interacting with the key sites important for enzyme activity according to the molecular docking study. Abstract : Increasing acetylcholine levels in brain through cholinesterase inhibition is a major strategy against Alzheimer's disease. Numerous scaffolds, including benzothiazolones, possessing potent cholinesterase inhibitory effects were reported. Thus, we designed and synthesized new benzothiazolone derivatives (6 a –i), one of which (6 f ) showed excellent BChE inhibition (IC50 =12.25 μM). Molecular docking rationalized 6 f 's potency by predicting substrate‐like binding in BChE active site.